2019
DOI: 10.18510/hssr.2019.7399
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Advertisement and Purchase Intention on Halal Cosmetic Products in Malaysia

Abstract: Purpose of the Study: The aim of this paper is to examine the relation between Muslim women customer offense caused due to Islamic advertising of halal cosmetic products in Malaysia. Methodology: The violation of Islamic ethics on the advertisement of halal cosmetic products and purchase intention was examined through a survey that included 110 Muslim women respondents in Malaysia who used cosmetics. The items used for the operationalization of variables were based on the advertising ethics provided by Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…From the perspective of studies in Malaysia, according to Hussin et al (2013a), five factors will affect the consumer purchase intention, which are brand, price, quality, ingredients, and labelling. Meanwhile, according to Arbak et al (2019b), there is a relationship between advertisement and halal cosmetics in their studies. This is because the advertisement will affect the consumer's purchase intention to buy halal products.…”
Section: Purchase Intention On Halal Cosmeticmentioning
confidence: 99%
“…From the perspective of studies in Malaysia, according to Hussin et al (2013a), five factors will affect the consumer purchase intention, which are brand, price, quality, ingredients, and labelling. Meanwhile, according to Arbak et al (2019b), there is a relationship between advertisement and halal cosmetics in their studies. This is because the advertisement will affect the consumer's purchase intention to buy halal products.…”
Section: Purchase Intention On Halal Cosmeticmentioning
confidence: 99%
“…The previous researchers used quantitative methods by using questionnaires to test their hypotheses about the relationship between the factors affecting purchase intention towards Halal products. However, only one study conducted by Arbak et al (2019) used a mixed-method, questionnaires, and interviews with the respondents. The respondents' numbers ranged from 63 respondents (Nurzulain et al, 2019) to 2931 respondents (Soon & Wallace, 2017).…”
Section: Overview Of the Previous Studymentioning
confidence: 99%
“…One paper, however, found that price does not influence customers' intention to buy Halal products. Arbak et al (2019) uniquely examined the role of advertisement, which includes contents such as honesty, language, sexism, and racism, affecting the purchase intention of halal cosmetics. To attract and retain consumers in Malaysia, marketers must avoid offending consumers by following Islamic advertising ethics.…”
Section: Pricementioning
confidence: 99%
“…Some of the international makeup producers and manufacturers did not apply for halal certification or halal logo on their products (Arbak et al, 2019). Given the significance of halal labelled cosmetics, the implementation of halal logo and marketing strategies are still hardly in place in the Malaysian cosmetics industry (Majid et al, 2015).…”
Section: Halal Certificationmentioning
confidence: 99%